Tungsten oxide ion-gated phototransistors using ionic liquid and aqueous gating media - De Oliveira Silval, Gabriel Vinicius; Subramanian, Arunprabaharan; Meng, Xiang; Zhang, Shiming; Barbosa, Martin S. [UNESP]; Baloukas, Bill; Chartrand, Daniel; Gonzales, Juan C.; Orlandi, Marcelo Ornaghi [UNESP]; Soavi, Francesca; Cicoira, Fabio; Santato, Clara (Iop Publishing Ltd, 2019)
Ion-gated transistors employ ionic gating media (e.g. ionic liquids, polymer electrolytes, aqueous saline solutions) to modulate the density of the charge carriers in the transistor channel. Not only they operate at low voltages (ca 0.5-1 V) but they can also feature printability, flexibility and easy integration with chemo- and bio-sensing platforms. Metal oxides are transistor channel materials interesting for their processability in air, at low temperature. Among metal oxides, tungsten oxide (band gap ca 2.5-2.7 eV) stands out for its electrochromic, gas sensing and photocatalytic properties. Here we demonstrate ion-gated tungsten oxide transistors and phototransistors working in different ion gating media, such as one hydrophobic ionic liquid and an aqueous electrolyte, fabricated both on rigid and flexible substrates. Ion-gated tungsten oxide phototransistors operating in aqueous media could be used as photocatalytic sensors in portable applications.
Keywords: ionic liquids; tungsten oxide; ion-gated transistors; phototransistors; polyimide